Brine film thicknesses on mica surfaces under geologic CO2 sequestration conditions and controlled capillary pressures. Issue 8 (26th August 2013) - Kim, Tae Wook; Tokunaga, Tetsu K.; Bargar, John R.; Latimer, Matthew J.; Webb, Samuel M.
Abstract : [1] Brine films remaining on mineral surfaces in deep reservoirs during CO2 sequestration are expected to influence multiphase flow, diffusion, and reactions, but little is known about their behavior. Using synchrotron X‐ray fluorescence (XRF), we measured thicknesses of KCsI2 brine films on two difference roughness mica surfaces under conditions representative of geological CO2 sequestration (7.8 MPa and 40°C) to understand the influences of mineral surface roughness and capillary potential. Brine thicknesses measured on the Mica 1 (smooth) and Mica 2 (rough) mica surfaces ranged from 23 to 8 nm and 491 to 412 nm, respectively, over the small range of tested capillary potentials (0.18–3.7 kPa). Within these potentials, brine film thicknesses on mica were governed by surface roughness and only weakly influenced by capillary potentials. In comparing drainage and rewetting isotherms, some film thickness hysteresis was observed, possibly indicative of changes in mica wettability. Key Points: Influences of surface roughness and capillary pressure on brine films on mica The hysteresis on both mica surfaces may be related to contact angle hysteresis The comparisons between experimental data and DLVO theory